Uncut interposed jejunum pouch versus esophago-gastrostomy and double anastomoses of jejunum to the esophagus and residual stomach: An innovative method of digestive tract reconstruction following proximal gastrectomy - JiaQing Gong; Xia Liu; GuangLan Wang; Wei Li; GuoDe Luo; Yan Lin; Bin Zhang; ChuanDong Chen (Asian Journal of Surgery, 2023)
Aim: An innovative method of digestive tract reconstruction following proximal gastrectomy, the uncut interposed jejunum pouch, esophagus and residual stomach double anastomosis(Uncut-D), was established in recent years. In order to fully clarify the superiority of the procedure, this study has conducted a systematic analysis and thorough discussion. Methods: 118 patients with adenocarcinoma of the esophagogastric junction who underwent proximal gastrectomy were enrolled in this study. According to the methods of digestive tract reconstruction, these patients were divided into three groups: Uncut-D(n = 43), esophagogastrostomy (EG, n = 36), jejunal interposition (JI, n = 39).The preoperative indicators, surgical complications and related indicators of postoperative quality of life were analyzed. Results: There were no significant differences in preoperative data among all groups (P > 0.05); The digestive tract reconstruction time in Uncut-D group was more than that in EG group, and less than that in JI group (P < 0.05). The incidence of esophageal anastomotic stenosis in Uncut-D group was significantly lower than that in EG group (P < 0.05); In Uncut-D group, the incidence of reflux esophagitis, postoperative nutrition index(PNI), weight recovery and Visick classification were significantly better than those in EG group (P < 0.05), furthermore, the incidence of delayed gastric emptying,PNI and weight recovery were better than those in JI group (P < 0.05). Conclusions: The Uncut-D procedure gave full play to jejunal continuity and the advantages of pouch, and played a valuable role in gastric and cardiac replacement, which significantly reduced long-term complications, improved postoperative nutritional status of patients and long-term quality of life.